Characterisation of the commercial pig as a model of musculoskeletal ageing and osteoarthritis - Macfadyen, Mhairi A. (2018)
Animal models of musculoskeletal ageing are required for the investigation of a number of conditions which may be difficult or unethical to investigate in humans. For this purpose, rodent models have been widely utilised, however, there are a number of differences between rodents and humans which may limit their usefulness as a model of human disease. Osteoarthritis (OA) is a musculoskeletal joint disorder characterised by degenerative loss of the articular cartilage and bone remodelling. In attempting to better understand the processes that mediate cartilage degeneration animal models have been utilised, however, OA in these models is typically induced either chemically or surgically and poorly mimics the pathological features of human OA. Spontaneous models also exist, one such model is the Dunkin Hartley guinea pig, but questions have been raised about the utility of these models due to issues with translatability of research into meaningful treatments in humans. Therefore, in order to better understand the key drivers of musculoskeletal decline and to identify and develop new therapeutics there is a high unmet need to develop more translatable animal models of musculoskeletal ageing. Importantly, the pig shares a high degree of physiological and anatomical similarity with that of humans and as a result, the pig is considered more closely related to humans than any other non-primate mammalian species. The high prevalence of degenerative joint conditions including osteochondrosis and osteoarthritis in commercial pig breeds suggests that these animals may represent an improved model. Therefore, in this study we assessed whether the commercial pig might present an alternative model of musculoskeletal ageing and early OA. For this purpose, this study investigated commercial pigs at a number of ages up to 4yrs paying particular attention to body composition changes, muscle changes and knee OA development within the age range. The utility of porcine cartilage and bone for ex-vivo studies was also examined. The investigation of body composition changes in these pigs did not reveal significant age-related deterioration, likewise, in muscle, no indication of early sarcopenic changes were identified. Together these findings suggest that the pigs used in this study were too young to be undergoing age-related muscle decline. Examination of OA in porcine knee joints revealed development of OA-like lesions and proteoglycan loss suggesting that these commercial pigs spontaneously develop OA at a relatively young age. Similarities between porcine and human cartilage and bone were also revealed with loss of chondrocyte phenotype in 2D culture and the discovery of an altered osteoblast phenotype in cells obtained from older, damaged knee joints; this osteoblast phenotype was similar to that found in sclerotic human bone. In summary, this work has shown that commercial pigs within this age range are too young to exhibit early indications of age-linked muscle decline, such as sarcopenia. However, pigs within this age range exhibit early OA changes in the knee joint and both porcine cartilage and bone may be of use in ex-vivo studies investigating OA. Together this suggests that pig could represent an appropriate animal model for the investigation of early OA.